Breast metastasis from lung adenocarcinoma: a case report and review of the literature - Ding, Jialing; Gu, Huayan; Yang, Zhi; Lu, Yiqiao; Guo, Guilong (Frontiers in Oncology, 2024)
Lung cancer (LC) is one of the most lethal and most prevalent malignant tumors, and lung adenocarcinoma (LUAD) is the most common pathological type of lung cancer. 1 Breast cancer (BC) is the most common cancer worldwide 2 , but metastases to the breast from extramammary neoplasms are rare 3 , especially from lung. Early diagnosis and differentiate primary from metastatic breast carcinoma are essential. Here, we present a case of metastases to the breast from lung adenocarcinoma, the treatment options varied according to disease progression.